A reliable and energy-efficient outdoor localisation method for smartphones. (2016) - Lin, Anhua; Zhang, Jianzhong; Jiang, Xiangzhou; Zhang, Jingya
Location has become a key service for smartphone applications. Nowadays, GPS and network-based technology have been widely used to provide location service. However, the former suffers its high power consumption, and the latter has some imperfections in location accuracy. In this paper, we present a reliable and energy-efficient localisation system using inertial sensors commonly found on today's smartphone. We first give an overall view of the localisation system, and then describe the key components separately. Furthermore, reliable algorithms for displacement determination and heading direction have been developed, and Vincenty's formulae are used to calculate the location of the endpoint. Location error correction mechanisms are also proposed to prevent accumulated error. Evaluation on Samsung I9100 in the real condition confirm anticipated benefits, and results show that ACMG uses 24.7% less power than GPS, and get a mean location accuracy of less than 6.7m in the playground of Nankai University.